PENGARUH PEMANFAATAN SUMBER BELAJAR TERHADAP HASIL BELAJAR SOSIOLOGI KELAS XI IIS SMA NEGERI 1 PEMANGKAT - Artina Artina; Izhar Salim; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research was to determine how the influence of the use of learning resources by students on learning outcomes of sociology subjects in class XI IIS SMA Negeri 1 Pemangkat. The research method used was a descriptive method with a form of relationship study research. Data collection techniques were through questionnaires and documentation studies. The research sample consisted of 64 students who were taken using simple random sampling. The results showed that the use of learning resources by class XI IIS students at SMA Negeri 1 Pemangkat was good enough. The results of simple linear regression analysis using the SPSS 20.0 program showed the effect of learning resources (X) on learning outcomes (Y) with the formulation Y = 42.906 + 0.461X. Based on SPSS 20.0 program calculations, t count was 6.741, the significance level was 0.000 and t table was 1.998. The value of t arithmetic ? t table (6,741 ? 1,998) then Ho is rejected and Ha is accepted. The coefficient of determination in this study showed that the contribution of the influence of variable X (learning resources) to variable Y (learning outcomes) is low in sociology subjects in class XI IIS, namely 0.257 or 25.7% while 74.3% is influenced by other variables.Keywords: Learning Resourches, Learning Outcomes, Sociology Subject.